Strategies for Sustainable Rural Tourism Innovation: Evidence from Hanoi, Vietnam - VU DINH, Hoa; NGO ANH, Tuan; NGUYEN THI NGOC, Anh; NGUYEN THI, Chi (Journal of Environmental Management and Tourism, 2023)
Rural tourism is an important driving force for developing rural areas that often face many challenges regarding economics, society, and the environment. Innovation in sustainable rural tourism is the basis for enhancing regeneration in tourism, meeting the goals of sustainable development, satisfying the needs of tourists, and enhancing economic, social, and environmental efficiency for rural areas. The research provides an in-depth understanding of sustainable rural tourism innovation. Therefore, it contributes to a better understanding of sustainable rural tourism innovation, which has not been extensively studied by researchers. Furthermore, it provides a typical case study of rural tourism innovation in a central urban area of developing countries, contributing to a better understanding of innovation in rural tourism destinations in developing country urban areas. The research also provides managers and policy-makers with insights that can be considered when building and implementing future rural tourism destination innovation policies.